In vitro immunological cross-reactivity of thai polyvalent and monovalent antivenoms with asian viper venoms - Chaisakul, Janeyuth; Muhamad Rusdi Ahmad Rusmili, Muhamad Rusdi; Alsolaiss, Jaffer; Albulescu, Laura-Oana; Harrison, Robert A.; Othman, Iekhsan; Casewell, Nicholas R. (MDPI, 2020)
The intravenous administration of polyclonal antibodies known as antivenom is the only effective treatment for snakebite envenomed victims, but because of inter-specific variation in the toxic components of snake venoms, these therapies have variable efficacies against different snake species and/or different populations of the same species. In this study, we sought to characterize the in vitro venom binding capability and in vitro cross-neutralizing activity of antivenom, specifically the Hemato Polyvalent antivenom (HPAV; The Queen Saovabha Memorial Institute (QSMI) of the Thai Red Cross Society, Thailand) and three monovalent antivenoms (QSMI) specific to Daboia siamensis, Calloselasma rhodostoma, and Trimeresurus albolabris venoms, against a variety of South Asian and Southeast Asian viper venoms (Calloselasma rhodostoma, Daboia russelii, Hypnale hypnale, Trimeresurus albolabris, Trimeresurus purpureomaculatus, Trimeresurus hageni, and Trimeresurus fucatus). Using ELISA and immunoblotting approaches, we find that the majority of protein components in the viper venoms were recognized and bound by the HPAV polyvalent antivenom, while the monospecific antivenom made against T.albolabris extensively recognized toxins present in the venom of related species, T. purpureomaculatus, T. hageni, and T. fucatus. In vitro coagulation assays using bovine plasma revealed similar findings, with HPAV antivenom significantly inhibiting the coagulopathic activities of all tested viper venoms and T. albolabris antivenom inhibiting the venoms from Malaysian arboreal pit vipers. We also show that the monovalent C. rhodostoma antivenom exhibits highly comparable levels of immunological binding and in vitro venom neutralization to venom from both Thailand and Malaysia, despite previous reports of considerable intraspecific venom variation. Our findings suggest that Thai antivenoms from QSMI may by useful therapeutics for managing snake envenomings caused by a number of Southeast Asian viper species and populations for which no specific antivenom currently exists and thus should be explored further to assess their clinical utility in treating snakebite victims